Synthesis and characterization of nano Fe2CuAl2O7 as a reusable catalyst for Biginelli reaction - Keshtiban Marzieh M.; Nikoo Abbas; Massoumi Bakhshali (Journal of the Serbian Chemical Society, 2025)
In this research, the novel mixed metal oxide nanoparticles (NPs) Fe2CuAl2O7 were synthesized by applying sol-gel auto-combustion method. The Fe2CuAl2O7 NPs were identified by XRD, FT-IR, Mapping and EDS. The XRD pattern showed that Fe2CuAl2O7 NPs contain a crystalline structure and have just one phase, and types of crystals are FCC. The size distribution of Fe2CuAl2O7 NPs was determined by FESEM to be about 41.44 nm. Using the BET equation, the surface area of Fe2CuAl2O7 NPs was calculated as 26.174 m2 g-1. Fe2CuAl2O7 NPs were used as a catalyst for the Biginelli reaction. 3,4- -Dihydropyrimidine-2(1H)-one/thione derivatives were prepared in the presence of Fe2CuAl2O7 nanocatalyst with short time and 75–97 % efficiency in water. In addition, the recovery and the reuse of the Fe2CuAl2O7 nanocatalyst was done up to five times without significant change in catalytic ability.